Research on multi-dimension features of application layer multicast protocols - LIAO Hai-ning; LU Xi-cheng (Tongxin xuebao)
A set of application layer multicast protocols were described and classified based on some properties such as data forwarding policy,service model,optimization objectives,optimization techniques,and fault mechanism.Then some recommendations were provided about the design of ALM protocols.Finally some important directions for future re-search are discussed.